Growing food in the garden - Stier, Catherine; Pottage, Floss (Chicago, Illinois : Albert Whitman & Company, 2022)
Inspired by trip to the farmer's market, Daniel decides to learn more about plants and joins the local community garden.
Ages 4-8.
Grades 2-3.
Keywords: Community gardens -- Fiction; Gardening -- Fiction; Plants -- Fiction